THE ABSENCE OF A HEGEMONIC STATE IN THE YAOUNDE CODE OF CONDUCT REGIME IN THE GULF OF GUINEA - Rahman, Maulana Ammar Auliaur (Global: Jurnal Politik Internasional, 2024)
In 2013, countries around the Gulf of Guinea established the Yaounde Code of Conduct as a maritime security regime to prevent and counter piracy and other maritime-related problems in the area. It turned out that numerous challenges made the Yaounde Code of Conduct unable to deal with the piracy problem in the area. This research, therefore, aims to explain the Yaounde Code of Conduct’s inability to deal with the problem using the Hegemonic Stability Theory, which is rooted in a power-based approach from international regimes study. By implementing explanative methods, the author argued that the absence of a hegemonic state in the Yaounde Code of Conduct regime made it unable to solve the piracy problem in the Gulf of Guinea. It is also important to examine the potential figure among the regime members to claim the hegemonic state position within the regime and the challenge that made them unable to claim that position yet.